Produção oral e crenças: a competência linguístico-comunicativa de egressos de um curso de letras espanhol EaD - Gonçalves, Angélica Ilha (2019)
Since the establishment of the Open University of Brazil in 2006, numerous distance learning graduate courses have been offered by public universities in the country, such as Spanish Language graduations. Considering that there are still few studies that focus on the formation of language teachers in this modality, this doctoral thesis aimed to investigate the associations between the proficiency level of the oral ability of egresses of a distance learning Spanish Language course and their beliefs about the linguistic-communicative competence, about the their teaching-learning process of this competence in DE and the beliefs of some of its teachers. To achieve these purposes, the following specific objectives were defined: (1) to identify the beliefs of graduates of a distance learning Spanish Letters course on the teaching-learning process of oral skills through this modality; (2) raise the beliefs about the own linguisticcommunicative competence of the graduates who were, at the time of the research, in professional practice; (3) identify the level of oral skill proficiency developed by the graduates who acted as teachers; (4) to analyze the possible relationships between oral proficiency levels and their beliefs and (5) to investigate the possible relations between the beliefs of graduates and teachers (dissertation / 2013) about the teaching-learning of oral skills in distance education. Thus, three research questions guided the work: (a) what are the beliefs of graduates of a distance learning Spanish Language course about their own language-communicative competence and about their development in DE? (b) What is the level of oral skill proficiency developed by these graduates in DE? (c) What are the possible relationships between the beliefs of these graduates and some of their teachers? To answer these questions and achieve the proposed objectives, three data collection instruments were used: questionnaire, interview and conversation record. As the thesis was based from the dissertation of Gonçalves (2013), relationships were established between the beliefs of the teachers participating in this research, who worked in the Spanish I discipline, and the thesis participants who were students of those teachers. The results showed that the most of the graduates who attended from all stages of the research, demonstrated to be in intermediate superior and advanced levels, reaching the level expected by the course according to the pedagogical project of the course (PPC). However, demonstrated that a greater number of communicative activities would be lacking, with greater frequency and quality of interactions to ensure the development of this competence by all students. Furthermore, it is still necessary to ensure teachers' preparation for the recognition of the most appropriate tools and resources for distance learning and teaching, as well as the understanding of how to provide effective and high-level interaction.